Case Report: Pediatric Ocular Ischemia and Neovascular Glaucoma in Neurofibromatosis Type 1. Issue 5 (3rd May 2022) - Selvan, Harathy; Surve, Abhidnya; Sharma, Sanjay; Venkatesh, Pradeep; Sihota, Ramanjit
Abstract : SIGNIFICANCE: Neovascular glaucoma is an important subset of secondary glaucoma in neurofibromatosis patients. Vasculopathy of the ophthalmic circulation needs to be borne in mind while evaluating their etiology. PURPOSE: This study aimed to report the presentation, diagnostic work-up and management of an unusual case of neovascular glaucoma in a child. CASE REPORT: A 7-year-old boy presented with uniocular ischemic fundus and secondary neovascular glaucoma. Detailed family history and evaluation led to a diagnosis of familial neurofibromatosis type 1. Fundus fluorescein angiography revealed compromised retinal and choroidal circulations in the affected eye. Ocular ultrasound B scan and neuroimaging did not show any contributory lesions. Cardiovascular evaluation was within normal limits. Ophthalmic Doppler imaging revealed normal proximal ophthalmic arteries in both eyes; however, the central retinal artery of the affected eye showed low flow in its proximal part and absent flow in the distal part, as compared with the fellow eye showing regular flow until the optic disc margin. Corroborating the clinical, fundus fluorescein angiography and Doppler findings, a diagnosis of neurofibromatosis type 1–related vasculopathy of the distal ophthalmic artery was made. Poor visual prognosis for the affected eye was explained, and anterior retinal cryopexy along with cyclocryotherapy was performed to treat the neovascular glaucoma. CONCLUSIONS: Vasculopathy of the ophthalmic circulation is an important cause of neovascular glaucoma in neurofibromatosis patients. The morphology of Lisch nodules may be altered in an ischemic eye, and therefore, careful examination of the other eye and systemic evaluation is vital in such unusual scenarios.